Extracellular Vesicles Derived From Regeneration Associated Cells Preserve Heart Function After Ischemia-Induced Injury - Salybekov, Amankeldi A.; Salybekova, Ainur; Sheng, Yin; Shinozaki, Yoshiko; Yokoyama, Keiko; Kobayashi, Shuzo; Asahara, Takayuki (Frontiers in Cardiovascular Medicine, 2021)
Under vasculogenic conditioning, pro-inflammatory cell subsets of peripheral blood mononuclear cells (PBMCs) shift their phenotype to pro-regenerative cells such as vasculogenic endothelial progenitor cells, M2 macrophages, and regulatory T cells, collectively designated as regeneration-associated cells (RACs). In this study, we evaluated the therapeutic efficacy of RAC-derived extracellular vesicles (RACev) compared to mesenchymal stem cell-derived EVs (MSCev) in the context of myocardial ischemia reperfusion injury (M-IRI). Human PBMCs were cultured with defined growth factors for seven days to harvest RACs. RACev and MSCev were isolated via serial centrifugation and ultracentrifugation. EV quantity and size were characterized by nanoparticle tracking analysis. In vitro, RACev markedly enhanced the viability, and proliferation of human umbilical vein endothelial cells in a dose-dependent manner compared to MSCev. Notably, systemic injection of RACev improved cardiac functions at 4 weeks, such as fractional shortening, and protection from mitral regurgitation than the MSCev-treated group. Histologically, the RACev-transplanted group showed less interstitial fibrosis and enhanced capillary densities compared to the MSCev group. These beneficial effects were coupled with significant expression of angiogenesis, anti-fibrosis, anti-inflammatory, and cardiomyogenesis-related miRs in RACev, while modestly in MSCev. In vivo bioluminescence analysis showed preferential accumulation of RACev in the IR-injured myocardium, while MSCev accumulation was limited. Immune phenotyping analysis confirmed the immunomodulatory effect of MSCev and RACev. Overall, repetitive systemic transplantation of RACev is superior to MSCev in terms of cardiac function enhancements via crucial angiogenesis, anti-fibrosis, anti-inflammation miR delivery to the ischemic tissue.